Supervisi Kepala Madrasah dalam Optimalisasi Potensi Guru Mata Pelajaran Fiqih di Madrasah Ibtidaiyah Negeri 2 Gresik - Achmad Anwar Abidin; Nor Mubin (Program Studi Manajemen Pendidikan Islam, 2021)
Supervision carried out at the madrassa level is s the responsibility of a madrassa head. This article discusses the madrassa head supervision model how it is efforts in optimizing the potential of existing teachers. This discussion is the result of research conducted at MIN 2 Gresik. Qualitative research with results that show that the supervision model carried out by the head of madrasah when supervising teachers of fiqh subjects is by using the clinical supervision model. Where the head of the madrassa observes firsthand the ongoing learning process in the supervised classroom. This is done so that the head of madrasah knows the readiness and preparation of teachers in the learning process, especially in fiqh subjects that require special skills related to ubudiyah practices. From this madrassa head will conduct follow-up as needed to optimize the potential of each teacher.